Narghile (water pipe) smoking among university students in Jordan: prevalence, pattern and beliefs - Dudeen Abdul-Aziz F; Abu-Hammad Shatha MK; Khraisat Ameen S; Eimar Hazem A; Al-Mashni Hamzeh M; Al-Omiri Mahmoud K; Bakri Faris G; Dar-Odeh Najla S; Abdallah Mohamed; Alkilani Samer; Al-Shami Louai; Abu-Hammad Osama A (BMC, 2010)
Abstract Background and objectives Narghile is becoming the favorite form of tobacco use by youth globally. This problem has received more attention in recent years. The aim of this study was to investigate the prevalence and pattern of narghile use among students in three public Jordanian universities; to assess their beliefs about narghile's adverse health consequences; and to evaluate their awareness of oral health and oral hygiene. Methods The study was a cross-sectional survey of university students. A self-administered, anonymous questionnaire was distributed randomly to university students in three public Jordanian universities during December, 2008. The questionnaire was designed to ask specific questions that are related to smoking in general, and to narghile smoking in specific. There were also questions about oral health awareness and oral hygiene practices. Results 36.8% of the surveyed sample indicated they were smokers comprising 61.9% of the male students and 10.7% of the female students in the study sample. Cigarettes and narghile were the preferred smoking methods among male students (42%). On the other hand, female students preferred narghile only (53%). Parental smoking status but not their educational level was associated with the students smoking status. Smokers had also significantly poor dental attendance and poor oral hygiene habits. Conclusion This study confirmed the spreading narghile epidemic among young people in Jordan like the neighboring countries of the Eastern Mediterranean region. Alarming signs were the poor oral health awareness among students particularly smokers.